Age-related decrease in functional mobility score when performing a locomotor task in an immersive environment - Renaux, Alexandre; Clanché, Fabien; Muhla, Frédéric; Duclos, Karine; Meyer, Philippe; Colnat-Coulbois, Sophie; Gauchard, Gérome (Frontiers in Bioengineering and Biotechnology, 2023)
In recent years, immersive virtual reality technology appeared in health field. Its use could make possible assessing motor behavior of individuals in adaptable and reproductible immersive environments, simulating real situations. This study aimed to assess the effect of an immersive scenario on functional mobility during a simple locomotor task according to age. Sixty young adults and sixty older people volunteers, autonomous, without cognitive and neurological impairment participated. A locomotor task based on the "Timed Up and Go" task was performed in real and virtual conditions. A functional mobility score was calculated by combining the time and the number of steps used and compared between young and older people. Results showed first that correlations between time and number of steps were the same in VR and real conditions, but the locomotor performance decreased significantly in VR condition for both populations. Second, older people reduced more their locomotor performance in virtual environment than young adults, thereby their functional mobility score decreased more to complete the task, reflecting the adoption of a more secure locomotion strategy often related to the fear of falling, with an increase in time and number of steps to support balance. The major difference between the real condition and the VR condition is the visual immersion through the use of an HMD and visual information is more important in the sensory integration of older people. Therefore, the reduction of visual field and the lack of visual exproprioceptive information about the body segments in the virtual environment could explain these results. Finally, the effect on mobility of being immersed in a virtual scenario exists for both populations but is accentuated by aging process and is therefore age-dependent.